SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI DARI SENYAWA 1-FENIL-3-(1-NAFTIL)-5-(2-KLOROFENIL)-2-PIRAZOLIN - Dahliarti '; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazoline is a bioactive compound but it is rare in nature. Pyrazoline has bioactivitieswhich are anti-inflammantory, antimicrobial, antibacterial, antidiabetic and antipyreticactivity. In this study this compound has been synthesized by reacting phenylhydrazinewith (E)-3-(2-chlorophenyl)-1-(naphtalen-1-yl)prop-2-en-1-one chalcone and thencatalyzed by acetic acid using microwave irradiation method. The yield of 1-phenyl-3-(1-naphtyl)-5-(2-chlorophenyl)-2-pyrazoline compound was 76,23%. This pyrazolinewas characterized using UV-Vis, IR, 1 H-NMR and 13 C-NMR spectrometer. Bioactivitytest showed that the pyrazoline compound does not have antibacterial activity againtGram-positive and Gram-negative bacteria.